Rheological, functional and thermo-physical properties of ultrasound treated whey proteins with addition of sucrose or milk powder - Anet Režek Jambrak; Vesna Lelas; Greta Krešić; Marija Badanjak; Suzana Rimac Brnčić; Zoran Herceg; Verica Batur; Iris Grčić (Mljekarstvo)
Ultrasound represents a non-thermal food processing technique and has great potential to be used in the food industry. The objective of this research was to observe ultrasound impact on physical properties of model systems prepared with whey protein isolates (WPI) or whey protein concentrates (WPC) with or without sucrose or milk powder addition. This kind of systems is often used in milk beverages and milk based products. Model systems with protein and milk powder or sucrose addition were treated with high power ultrasound (HPU) probe of 30 kHz frequency for 5 and 10 minutes. After sonication several properties were determined and examined: solubility, emulsifying and foaming properties, rheological and thermophysical properties. Ultrasound treatment showed severe influence on all examined properties, caused by protein denaturation as a consequence of cavitation and microstreaming effects. Ultrasound treatment caused decrease in protein solubility for whey protein isolate and whey protein concentrates model systems, compared to untreated sample. There was statistically significant increase in foam volume of model systems, prepared with sucrose or milk powder and WPI after ultrasound treatment. Statistically significant decrease in emulsion activity and emulsion stability indices was observed for model systems prepared solely with isolates and concentrates. After treatment of whey protein model systems (with or without milk powder or sucrose) with 30 kHz ultrasound, the changes in consistency coefficients (k) were observed, but there were no significant changes in flow behaviour indices (n). After addition of milk powder or sucrose, statistically significant decrease in initial freezing and melting temperatures was observed due to the ultrasound treatment.